Management Elements in the Management of Aston Kuta Hotel & Residence: Implementation and Strategies for Sustainability - Widari, Dewa Ayu Diyah Sri; Ampur, Maria Agusta Hipolita; Foglin, Maria Angelia Selvira; Nudin, Rafael Septiano; Ratna, Kristina Rati (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
This study examines the implementation of the 6M management framework (man, money, material, method, machine, market) and its strategic operationalization for sustainable business performance at Aston Kuta Hotel & Residence, Bali. Addressing a critical gap in hospitality literature which prioritizes marketing over core management systems. It employed a descriptive qualitative methodology with triangulated data collection (semi-structured interviews with 12 departmental managers, participatory observation, and organizational document analysis). Findings demonstrate that the hotel's sustainability strategy hinges on three operational pillars: (1) human capital optimization through competency-based training and performance incentives, (2) financial efficiency via predictive budgeting and resource allocation models, and (3) systematized asset management encompassing circular procurement protocols and preventive maintenance regimes. These practices substantiate the 6M framework's efficacy in achieving dual objectives: enhanced service quality and competitive resilience amidst Bali's saturated hospitality market. The research contributes to sustainable hospitality theory by operationalizing management elements as dynamic drivers of organizational viability, providing a replicable model for ASEAN 4-star hotels navigating resource-intensity challenges